Magnetic anomalies controlled by surficial dynamics and quaternary drainage patterns in volcanic-derived soils (Tuscania, Italy) - Casas-Sainz, Antonio M.; Román-Berdiel, Teresa; Villalaín, Juan J.; Castro-Priego, Manuel; Pérez-Polo, Marta; Pocoví, Andrés; Diarte-Blasco, Pilar (Journal of applied geophysics, 2025)
Magnetic anomalies in an agricultural area developed over volcanic-derived soils (Tuscania, Lazio region, Italy), resulting from both weathering of tuff and lava flows and transport of detrital grains, show a linear pattern with NW-SE direction and amplitudes between 40 and 100 nT in the intensity of the total field (some of them with dipolar geometry) and up to 50 nT in the vertical magnetic gradient. The location of anomalies partly correlates with the highs and lows of the magnetic susceptibility values measured in situ and from soil samples, that range from 2000 × 10−6 SI to 50000 × 10−6 SI. Magnetite is the main carrier of the magnetic susceptibility, as inferred from thermomagnetic curves, whose reversibility corroborates the volcanic origin of detrital particles. The anomalies obtained, although showing a somewhat irregular orthogonal pattern, are interpreted as the result of the differential concentration of magnetic minerals related to an ancient (Quaternary) drainage system. This is corroborated by the analysis of time-series of orthophotographs, which indicate that the drainage pattern developed in the stepped Quaternary piedmont levels located above the present-day thalwegs shows a geometry consistent with the magnetic anomalies. [Display omitted] •- Interpretation of magnetic anomalies in volcanic-derived soil.•- Magnetic properties are strongly dependent on grain size.•- Magnetite-bearing sands are the main contributors to magnetic susceptibility.•- Magnetic anomalies are (partly) linked to the Pleistocene fluvial network.